2006
DOI: 10.21101/cejph.a3378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Some Bacteria Yeasts and Molds in Meat Foods in San Luis, Argentina

Abstract: In this work we evaluate the microbiological quality and the hygiene degree of meat foods consumed in the city of San Luis. A total of 515 meat food samples (315 from fresh sausages, 100 from hamburgers and 100 from ground beef) were processed, being the most of them non-industrial products. The microbiological quality was determined by counts of total mesophilic bacteria, coliforms, Escherichia coli, molds and yeasts, and Clostridium perfringens. The number of total mesophilic aerobes was within the 10 6 cfu/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
7
9
0
Order By: Relevance
“…The results in Table (2) appeared that, the minimum and the maximum Enterobacteriaceae count in the examined fresh beef and meat products( minced meat ,sausage and luncheon )were ranged from 1.2×10 2 to 3.3×10 2 ; 1.1×10 2 to 2.9×10 2 ; 1.2×10 2 to 2.7×10 2 and 1.0×10 2 to 2.6×10 2 , respectively, with a mean value of 2.14×10 2 ±0.97×10 2 ; 2.02×10 2 ±0.76×10 2 ; 1.85×10 2 ±0.64×10 2 and 1.69×10 2 ±0.70×10 2 , respectively. These results of were agree with those of Hassan and Soultan (2004); Stagnitta et al (2006) and Gwida et al (2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results in Table (2) appeared that, the minimum and the maximum Enterobacteriaceae count in the examined fresh beef and meat products( minced meat ,sausage and luncheon )were ranged from 1.2×10 2 to 3.3×10 2 ; 1.1×10 2 to 2.9×10 2 ; 1.2×10 2 to 2.7×10 2 and 1.0×10 2 to 2.6×10 2 , respectively, with a mean value of 2.14×10 2 ±0.97×10 2 ; 2.02×10 2 ±0.76×10 2 ; 1.85×10 2 ±0.64×10 2 and 1.69×10 2 ±0.70×10 2 , respectively. These results of were agree with those of Hassan and Soultan (2004); Stagnitta et al (2006) and Gwida et al (2014).…”
Section: Discussionsupporting
confidence: 93%
“…73×10 2 ±0.08 ×10 2 and 0.71×10 2 ±0.07×10 2 , respectively. These results came in parallel with those of Paulsen et al (2006) Stagnitta et al (2006; Ahmed-Alyaa (2015); Al-Mutairi (2011) and Hamed et al (2015).…”
Section: Discussionsupporting
confidence: 81%
“…Coliform bacteria count revealed that all chicken luncheon samples were not more than 3 cfu/g. These results are in agreement with those obtained by Stagnitta et al (2006). Esherichia coli is not detected.…”
Section: Microbiology Examination Of Chicken Luncheon Samplessupporting
confidence: 93%
“…Data presented in Table (4) showed that, the value of coliform count of meat products (minced meat, kofta, burger and sausage) was 0.58×10 2 ±0.21×10 2 , 0.39×10 2 ±0.10×10 2 , 0.34×10 2 ±0.09×10 2 and 0.32×10 2 ±0.11×10 2 ,respectively. These results came in parallel with those of Paulsen et al (2006), Stagnitta et al (2006)., Al-Mutairi (2011)., and Heweidy (2017). Moreover, the statistical results revealed that, there were no significant difference (P>0.05) of total Coliform count between minced meat, kofta, burger and sausage samples.…”
Section: Total Coliform Countsupporting
confidence: 80%